(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article discusses the influence of digital communication on the formation of new lexical and grammatical models of the modern Russian language. The author analyzes the processes that occur as a result of the active use of instant messengers, social networks and network platforms. Special attention is paid to the phenomena of abbreviations, acronymization and hybridization of language units. The mechanisms of penetration of Internet jargon and Anglicisms into the everyday speech of native speakers are considered. grammatical structures, which manifests itself in the simplification of syntax and changes in the norms of the design of written speech. The role of the speed of information exchange as a factor influencing the economy of language resources is emphasized. Based on the analysis of digital discourses, new communicative strategies are identified, due to the specifics of virtual communication. The author shows that the digital environment is becoming an independent language space that forms its own norms and stylistic rules. The conclusion is made about the need for further study of the dynamics of Internet communication to understand the ways of development of the modern Russian language. It has been established that digital communication is beginning to have a systemic impact not only on vocabulary, but also on grammar. The paper emphasizes the importance of adapting linguistic analysis to the new conditions of language functioning.